Contribution of Mastery of Sociolinguistic Concepts to Pragmatic Skills by Students of Free Mathodist 1 Private Junior High School Medan 2012/2013 Academic Year - Nur Ayni M Pasaribu (Institute of Computer Science (IOCS), 2022)
Mastery of sociolinguistic concepts gives a negative contribution to the achievement of students' pragmatic skills. In accordance with the results of the analysis above, it can be concluded that the mastery of sociolinguistic concepts is not a criterion variable that makes a significant contribution to improving pragmatic skills. Thus, the research hypothesis which says that mastery of sociolinguistic concepts makes a significant contribution to the development of pragmatic skills of Free Methodist 1 Private Junior High School students, is not proven.